The Impact of Working Conditions on Productivity and Job Satisfaction in the Pharmaceutical Wholesaler Industry Economic - Mailani Khoironika; Oktri Mohammad Firdaus; Intan Tenisia Prawita Sari (Equity: Jurnal Ekonomi, 2025)
Rapid changes in the workplace and increasing job demands often affect employee well-being. One of the most common negative effects is burnout, usually characterized by mental, physical, and emotional exhaustion due to excessive workload. This study aims to determine the effect of workload and job demand on burnout, with mental health as a mediating variable, at PT Anna Mandiri Jaya. A quantitative approach was used with explanatory method and SEM-PLS analysis. Data was collected from 35 employees using an online questionnaire. From the results, we can see that workload and job demand have no significant direct impact on mental health. However, mental health has a significant effect on burnout, which shows its main role as a mediating variable. These results highlight the importance of maintaining employees' mental health to reduce the risk of burnout and recommend interventions such as stress management training, counseling, and a supportive work environment. This information can help companies in their efforts to improve employee well-being and productivity.